Prevalence of allergic sensitization, hay fever, eczema, and asthma in a longitudinal birth cohort - Owens, L.; Laing, I.; Zhang, Guicheng; Turner, S.; Le Souëf, P. (2018)
© 2018 Owens et al. Purpose: The aim of this study was to longitudinally assess the prevalence of allergic sensitization, asthma, eczema and hay fever from infancy to adulthood in a single cohort. Participants and methods: This prospective study is based on a longitudinal birth cohort of 253 participants, with respiratory and immunological assessments at 1, 6, 11, 18 and 24 years of age. Subjects were recruited from an urban maternity hospital. Retention rates varied from 45% to 72% at follow-up assessments. Asthma diagnosis was based on physician diagnosis of asthma and symptoms/medications in the previous 12 months. Allergic sensitization was defined by the positive skin prick test. Hay fever and eczema were based on a questionnaire. Results: The prevalence of allergic sensitization rose from 19% (n=33) at 1 year of age to 71% (n=77) at 24 years of age. The rate of asthma halved from 25% at 6 years of age to 12%–15% between 11 and 24 years of age, but the prevalence of allergic sensitization among those with asthma doubled from 50% at 6 years of age to 100% at 24 years of age. Hay fever rates rose throughout childhood from 7% at 6 years of age to 44% at 24 years of age, while the prevalence of eczema reduced from 25% at 6 years of age to 16% at 24 years of age. Parental atopy doubled the odds of asthma in their offspring by 24 years of age (odds ratio [OR]= 2.63, 95% CI 1.1–6.2, p=0.029). In all, 74% of those with asthma at 24 years of age also reported hay fever. The relationship between eczema and asthma was only significant up to 11 years of age, and the relationship between hay fever and asthma was stronger in adolescence and early adulthood than in early childhood. Conclusion: Patterns of atopic disorders vary throughout childhood. Although the prevalence of allergic sensitization and hay fever rose throughout childhood and the prevalence of asthma reduced, the strength of their relationship with asthma increased with age.